PERAN KELEMBAGAAN PETANI PADA ASPEK PRODUKSI DAN EKONOMI PETANI DI KELURAHAN NAIBONAT KABUPATEN KUPANG - Melgiana S. Medah; Siviardus Marjaya (Partner, 2023)
The aim of the study was to analyze the role of farmer diversity in production and economic aspects. The research method is descriptive qualitative with purposive sampling of 50 farmer respondents. The results showed the role of farmer groups in the production aspect, the highest was in the variable distribution of subsidized fertilizer assistance 90%, superior seeds 39%, while the variability of farmer group cultivation technology had no role. In the economic aspect, the highest role is in the variable source of information on commodity prices in the market by 84%. For marketing variables of agricultural products, farmer groups have not played a role, marketing of produce is carried out alone and controlled by middlemen. It can be concluded that the institutional role of farmers is still limited to the distribution of production input assistance from the government and as a source of price information. Keywords: Role, farmer institutions, production, economy